Experiential marketing and practices: The perspective of customer satisfaction and loyalty - Bayır, Talha (IGI Global, 2022)
Experiential marketing creates lasting happiness and satisfaction by influencing the desires and emotions of consumers at the point of transforming the product or service into utility and symbolic value. This study aims to look at the examples and outputs of experiential marketing, which is one of the important marketing approaches to achieving customer satisfaction and customer loyalty. For this purpose, the concept of experiential marketing, dimensions of experiential marketing, stages of customer experience management, experiential marketing practices (Starbucks, IKEA, Nike Town, Disneyland, and Abercrombie & Fitch) customer satisfaction, and customer loyalty are discussed theoretically in this study. Then, the effect of experiential marketing practices on customer satisfaction and customer loyalty is presented. Finally, theoretical information is presented that experiential marketing application examples are an important tool in creating permanent happiness and satisfaction by influencing the sense of pleasure of consumers in the conclusion part.